PENGARUH KEPRIBADIAN EXTRAVERT TERHADAP PERILAKU KONTRAPRODUKTIF GURU SMA NEGERI DI KECAMATAN MATRAMAN JAKARTA TIMUR - Rhoma Iskandar (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
The purpose of this research is to obtain information about the influence of extravert personality and distributive justice on counterproductive behavior teachers. This study uses a quantitative approach. This research was carried out using a quantitative survey with path analysis applied in testing hypotheses. Members of 95 teachers from high schools in Matraman Regency as samples were selected by simple random sampling. This study concludes: (1) There are direct negative effects of extravert personality on counterproductive behavior (2) There are direct negative effects of distributive justice on counterproductive behavior (3) There is a direct positive effect of extravert personality on distributive justice (4) There is a direct negative effect from extravert personality to counterproductive behavior through distributive justice.